2008
DOI: 10.1099/ijs.0.65504-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides xylanisolvens sp. nov., a xylan-degrading bacterium isolated from human faeces

Abstract: During the course of a study on the xylan-degrading community from the human gut, six xylanolytic, Gram-negative, anaerobic rods were isolated from faecal samples. 16S rRNA gene sequence analysis showed that the isolates were closely related to each other (¢99 % sequence similarity) and that they belonged to the genus Bacteroides. On the basis of 16S rRNA gene sequence similarity, representative strain XB1AT was most closely related to the type strains ofBacteroides ovatus (97.5 %), B. finegoldii (96.5 %) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
71
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 26 publications
4
71
0
1
Order By: Relevance
“…Some species of the genus Bacteroides, including Bacteroides thetaiotaomicron, are known to be decomposers in the colon by fermenting carbohydrates and catabolizing polysaccharides (hemicellulose and xylan) (Falony et al, 2009;Flint, 2006;Salyers, 1995;Van der Meulen et al, 2006). Novel strains of members of the genus Bacteroides from human faeces and intestinal organs have been identified using cultureindependent techniques based on 16S rRNA gene sequence analysis (Dore et al, 1998; Eckburg et al, 2005; Gill et al, 2006;Hayashi et al, 2003;Li et al, 2009;Palmer et al, 2007) and several novel species have recently been identified and characterized (Bakir et al, 2006a, b, c;Chassard et al, 2008; Hayashi et al, 2007;Kitahara et al, 2005;Robert et al, 2007;Song et al, 2004).In this study, two strains, designated MAJ27 T and MAJ26, were isolated from faeces of a healthy 26-year-old male during a Korean study on the diversity of cultivable intestinal microbiota. The strains were isolated on supplemented brain heart diffusion medium (BHIS) containing 50 mg kanamycin l 21 (Sigma) after 2 days at 37 u C in an anaerobic chamber (Bactron II; Shel Lab) containing N 2 /H 2 /CO 2 (90 : 5 : 5) (Bacic & Smith, 2008;Hecht, 2006;Smith et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some species of the genus Bacteroides, including Bacteroides thetaiotaomicron, are known to be decomposers in the colon by fermenting carbohydrates and catabolizing polysaccharides (hemicellulose and xylan) (Falony et al, 2009;Flint, 2006;Salyers, 1995;Van der Meulen et al, 2006). Novel strains of members of the genus Bacteroides from human faeces and intestinal organs have been identified using cultureindependent techniques based on 16S rRNA gene sequence analysis (Dore et al, 1998; Eckburg et al, 2005; Gill et al, 2006;Hayashi et al, 2003;Li et al, 2009;Palmer et al, 2007) and several novel species have recently been identified and characterized (Bakir et al, 2006a, b, c;Chassard et al, 2008; Hayashi et al, 2007;Kitahara et al, 2005;Robert et al, 2007;Song et al, 2004).In this study, two strains, designated MAJ27 T and MAJ26, were isolated from faeces of a healthy 26-year-old male during a Korean study on the diversity of cultivable intestinal microbiota. The strains were isolated on supplemented brain heart diffusion medium (BHIS) containing 50 mg kanamycin l 21 (Sigma) after 2 days at 37 u C in an anaerobic chamber (Bactron II; Shel Lab) containing N 2 /H 2 /CO 2 (90 : 5 : 5) (Bacic & Smith, 2008;Hecht, 2006;Smith et al, 2006).…”
mentioning
confidence: 99%
“…Some species of the genus Bacteroides, including Bacteroides thetaiotaomicron, are known to be decomposers in the colon by fermenting carbohydrates and catabolizing polysaccharides (hemicellulose and xylan) (Falony et al, 2009;Flint, 2006;Salyers, 1995;Van der Meulen et al, 2006). Novel strains of members of the genus Bacteroides from human faeces and intestinal organs have been identified using cultureindependent techniques based on 16S rRNA gene sequence analysis (Dore et al, 1998;Eckburg et al, 2005;Gill et al, 2006;Hayashi et al, 2003;Li et al, 2009;Palmer et al, 2007) and several novel species have recently been identified and characterized (Bakir et al, 2006a, b, c;Chassard et al, 2008;Hayashi et al, 2007;Kitahara et al, 2005;Robert et al, 2007;Song et al, 2004).…”
mentioning
confidence: 99%
“…Viable cells were not recovered from cultures held at 100 u C for 10 min and no spores were detected either in cellulose-or cellobiose-grown cultures incubated for more than 15 days at 37 u C. Strain 18P13 T was unable to grow on agar plates and was thus cultivated on agar medium using the roll-tube technique with 100 % CO 2 in the gas phase. Colonies on BC medium containing cellobiose were white with a brown centre, translucent, circular with entire margins and 1.5-2.5 mm in diameter after 24 h. DNA extraction, amplification and sequencing of the 16S rRNA gene of strain 18P13 T were performed as reported previously (Chassard et al, 2008a). Briefly, cells were grown for 24 h in 50 ml BC medium containing 2 g cellobiose l 21 , harvested by centrifugation and subjected to DNA extraction (Easy DNA kit; Invitrogen).…”
mentioning
confidence: 99%
“…DNA extraction, amplification and sequencing of the 16S rRNA gene of strain 18P13 T were performed as reported previously (Chassard et al, 2008a). Briefly, cells were grown for 24 h in 50 ml BC medium containing 2 g cellobiose l 21 , harvested by centrifugation and subjected to DNA extraction (Easy DNA kit; Invitrogen).…”
mentioning
confidence: 99%
“…The metabolic end products were prepared as described by Holdeman et al (1977) and analysed as described by Sakamoto et al (2005). Since strain Rs-03 T was isolated from a termite, and one of its closest phylogenetic relatives, Bacteroides xylanisolvens, is known to be xylanolytic (Chassard et al, 2008), the novel strain was tested for the degradation and fermentation of different polysaccharides including xylan (from oat spelts), soluble starch, carboxymethylcellulose and pectin (from citrus), using tubes that contained 10 ml peptone-yeast extract broth [PY; 1% (w/v) peptone, 1 % (w/v) yeast extract] and 50 mg polysaccharide. Cultures in these tubes were incubated at 37 uC for 4 days.…”
mentioning
confidence: 99%